2011
DOI: 10.1590/s0103-50532011001000020
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of allylic carbocations with benzene: a theoretical model of carbocationic intermediates in terpene biosynthesis

Abstract: Carbocátions atuam de formas diferentes quando interagem com anéis aromáticos. É interessante como na biosíntese de terpenos, os intermediários carbocatiônicos não alquilam a cadeia lateral aromática de aminoácidos presentes no sítio ativo, como seria esperado para outros carbocátions, como o cátion terc-butila. Neste trabalho, a interação entre benzeno e diferentes carbocátions alílicos é analisada, mimetizando carbocátions terpenóides, para melhor compreender como esta interação ocorreria. Cálculos em nível … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…One region of the wide spectrum of potential interactions remains both relatively unexplored and interesting to usnamely, the interaction of carbocationic centers with the π-faces of aromatic rings in proximity (Figure ). From a biochemical perspective, a few intriguing X-ray structural studies of enzymatic systems suggest that key aromatic amino acid residues play a role in stabilizing carbocation intermediates. , Being coordinatively unsaturated, carbocations are expected to interact somewhat differently with π-systems than ammonium cations, for example. On the other hand, experimental examples of chemical systems that explore the nature of carbocation−π interactions in aromatic systems are fairly rare …”
mentioning
confidence: 99%
“…One region of the wide spectrum of potential interactions remains both relatively unexplored and interesting to usnamely, the interaction of carbocationic centers with the π-faces of aromatic rings in proximity (Figure ). From a biochemical perspective, a few intriguing X-ray structural studies of enzymatic systems suggest that key aromatic amino acid residues play a role in stabilizing carbocation intermediates. , Being coordinatively unsaturated, carbocations are expected to interact somewhat differently with π-systems than ammonium cations, for example. On the other hand, experimental examples of chemical systems that explore the nature of carbocation−π interactions in aromatic systems are fairly rare …”
mentioning
confidence: 99%
“…Many recent studies using DFT‐calculations have revealed the possibility of the existence of semiconductive carbon structures. A metastable semiconductive ABF ‐Carbon structure was predicted, based on the connection of sp 3 carbon atoms and the spiropentadiene molecular motif, with a thermal stability up to 900 K [87] . This structure is formed by 6 carbon atoms (2 sp 2 and 4 sp 3 ), possessing a direct bandgap of 2.39 eV and higher cohesive energy in comparison with Y‐Carbon/1‐diamondyne and T‐Carbon.…”
Section: Liquid Metallic and Semiconductive Carbonmentioning
confidence: 99%
“…Many recent studies using DFTcalculations have revealed the possibility of the existence of semiconductive carbon structures. A metastable semiconductive ABF-Carbon structure was predicted, based on the connection of sp 3 carbon atoms and the spiropentadiene molecular motif, with a thermal stability up to 900 K. [87] This structure is formed by 6 carbon atoms (2 sp 2 and 4 sp 3 ), possessing a direct bandgap of 2.39 eV and higher cohesive energy in comparison with Y-Carbon/1-diamondyne and T-Carbon. Another important example of this class is curved 6.8 2 D carbon (Figure 32), which is an indirect bandgap semiconductor with a 3D structure consisting of all sp 2 hybridized carbon atoms (electrons are localized in the middle of CÀ C bonds) with negative curvature and high-temperature dynamic stability.…”
Section: Liquid Metallic and Semiconductive Carbonmentioning
confidence: 99%
“…In the absence of some type of isomerization, the only product would be 2‐phenyl dodecane. A number of papers discuss possible structures for pi‐complexes, as well as the nature of the binding that holds them together, but we are unaware of any studies related to the rates at which these cationic species isomerize.…”
Section: Introductionmentioning
confidence: 99%